1989
DOI: 10.1111/j.1365-2125.1989.tb05356.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint pain and quality of life; results of a randomised trial.

Abstract: 1. Eight hundred and forty‐six patients with pain in one or two joints of the hip, knee, ankle or wrist participated in a randomised double‐ blind trial to compare the efficacy, tolerability and effect on quality of life of diclofenac sodium slow release (DSR) 100 mg daily and a combination of dextropropoxyphene 180 mg and paracetamol 1.95 g daily (D&P). Health status or quality of life was measured using the Nottingham Health Profile (NHP) questionnaire. 2. Pain as measured by a visual analogue scale (VAS) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 8 publications
0
17
0
7
Order By: Relevance
“…Parr et al5found a smaller effect than that estimated in either comparison by Bradley et al,6 and slightly smaller than that found by Williams et al7 This may be because patients in the general practice population in the Parr study were less severely affected than those in other trials, who were recruited from secondary care, or it may reflect different inclusion criteria. Both the Bradley and Williams studies required a definite diagnosis of osteoarthritis, while the Parr study did not.…”
Section: Evidence From Randomised Trialsmentioning
confidence: 73%
See 1 more Smart Citation
“…Parr et al5found a smaller effect than that estimated in either comparison by Bradley et al,6 and slightly smaller than that found by Williams et al7 This may be because patients in the general practice population in the Parr study were less severely affected than those in other trials, who were recruited from secondary care, or it may reflect different inclusion criteria. Both the Bradley and Williams studies required a definite diagnosis of osteoarthritis, while the Parr study did not.…”
Section: Evidence From Randomised Trialsmentioning
confidence: 73%
“…Three trials (four comparisons), in which a total of 969 patients were randomised to simple analgesia or a non-steroidal anti-inflammatory drug, examined pain at rest by using a visual analogue scale5,7 The pooled standardised weighted mean difference was 0.35 (95% confidence interval 0.17 to 0.53), indicating that non-steroidal anti-inflammatory drugs were slightly more effective than simple analgesia (fig 2). We found evidence of heterogeneity (Q=6.69; df=3; P=0.08), confirming the appropriateness of the random effects model.…”
Section: Evidence From Randomised Trialsmentioning
confidence: 99%
“…Unlike the opioids the NSAIDs do not demonstrate tolerance, and they often are more effective at controlling certain pain conditions with fewer side effects than the opioids. 13 They have even demonstrated clear clinical utility in such severe pain states as metastatic spread of cancer to bone usually supplementing rather than replacing the role of opioids. 14 In one study, 15 it was found that Ketorolac exhibits significant opiate-sparing effects in the immediate postoperative period without introducing additional morbidity to paediatric surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…D. Parr и соавт. [63] в 8-недельном РКИ провели сравнение лечебного действия диклофенака 100 мг/сут и декстропоксифена в дозе 180 мг/сут (в комбина-ции с парацетамолом 2 г/сут) у 846 больных ОА. Диклофенак оказался достоверно эффективнее -снижение выраженно-сти боли было в среднем больше на 8% (р=0,05), а улучше-ние физической активности -на 13% (р=0,01).…”
Section: « д е с я т ь ш а г о в » : а л г о р и т м д л и т е л ь н unclassified